Arctic Species Trend Index: Tracking Trends in Arctic Vertebrate Populations Through Space and Time - Böhm, M; McRae, L.; Delnet, S.; Gill, M.; Collen, B. (Conservation of Arctic Flora and Fauna (CAFF), 2012)
"Utilizing the ASTI data (890 vertebrate populations from 323 species spanning a time period from 1951 to 2010), we expanded the original investigation to examine broad-scale spatial patterns of biodiversity change across the Arctic. These patterns were looked at in relation to climatic and other environmental data to investigate potential causal mechanisms of biodiversity change. As well, we evaluated the spatial distribution and quality of biodiversity monitoring across the Arctic for use in identifying critical gaps in monitoring coverage. This report builds on The Arctic Species Trend Index 2010: Tracking trends in Arctic wildlife, which provided our first broad measure of trends in vertebrate populations at a pan-Arctic scale."